Optimization of The Pump Room Layout Using Ergonomic Analysis and Maintenance Accessibility in The XYZ Project - Wayan Kaliya Krisna; Anak Agung Istri Agung Sri Komaladewi; I Gusti Ngurah Priambadi (International Journal Labs, 2026)
The pump room is one of the utility areas that plays an important role in supporting building operations. A pump room layout that does not consider ergonomic aspects and maintenance accessibility may limit operator movement, create difficulties in accessing equipment, and increase the risk of musculoskeletal disorders. This study aims to optimize the pump room layout in the XYZ Project through an ergonomic approach and maintenance accessibility assessment to improve safety, comfort, and work efficiency. The research methods include field observations, room and equipment dimension measurements, anthropometric analysis, maintenance accessibility evaluation, and work posture assessment using the Rapid Entire Body Assessment (REBA) method. The results show that the existing layout still has limited operator movement space, excessively close distances between equipment, and suboptimal maintenance access. The REBA assessment results indicate an ergonomic risk score of 11 for water tank inspection and pump strainer cleaning activities, a score of 10 for checking piping system leaks, a score of 9 for valve operation, and a score of 6 for checking the control panel. Based on the analysis results, a layout redesign was carried out by considering anthropometric data and maintenance space requirements. The redesign improved accessibility, facilitated maintenance activities, and enhanced operator working conditions. The results of the study indicate that ergonomics-based pump room layout optimization can reduce the risk level of musculoskeletal disorders, as shown by the REBA analysis, increase maintenance accessibility, and support the overall operational efficiency of the pump room.